Education in a digital world : global perspectives on technology and education - Selwyn, Neil. (New York : Routledge, 2013)
"The book takes a comprehensive look at digital technology use in educational settings around the world. Drawing on a wealth of theoretical and empirical work, the book tackles a number of pressing questions"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Educational technology -- Cross-cultural studies; Education and globalization -- Cross-cultural studies; Computer-assisted instruction -- Cross-cultural studies; Electronic books